Observation guide for the partial practical exam of the Respiratory and Cardiovascular Systems in Introduction to the Clinic - Rubén Dario García Núñez; María Aurelia San Juan Bosch; Esteban Jesús Sánchez Martínez; Carla María García San Juan; José Demián Rodríguez Medina (Medisur)
Background: the practical examination constitutes the moment in which the acquisition of communication skills, the physical examination of healthy individuals, as well as the transcription of the findings is verified. The difficulties that have existed in the development of this activity and the lack of homogeneity in its application, together with the high number of excellent evaluations when applying it, make it necessary to establish a guide for its execution. Objective: to design an observation guide for the partial practical exam of the Respiratory and Cardiovascular Systems in Introduction to the Clinic. Methods: exploratory, descriptive and cross-sectional research work was carried out using the method of documentary analysis based on the following documents review: Resolution 02/2018, Program of the subject Introduction to the Clinic, the Integrative Main Discipline Program and the method of participatory scientific observation. Results: the observation guide consists of three blocks, the first of communication, the second execution of the physical examination and the third transcription, which are evaluated and scored independently. The way to evaluate each block and the methodology to be followed is proposed and explained. Conclusions: the proposed guide will allow raising the quality and rigor, as well as a greater preparation of the students to carry out the physical examination of the Respiratory and Cardiovascular Systems. Its use constitutes a key element in the partial evaluation of the subject.